Autistic Symptoms in Schizophrenia Spectrum Disorders: A Systematic Review and Meta-Analysis - De Crescenzo, Franco; Postorino, Valentina; Siracusano, Martina; Riccioni, Assia; Armando, Marco; Curatolo, Paolo; Mazzone, Luigi (Frontiers in Psychiatry, 2019)
BACKGROUND: Recent studies have examined the association between autism spectrum disorder and schizophrenia spectrum disorders, describing a number of cognitive features common to both conditions (e.g., weak central coherence, difficulties in set-shifting, impairment in theory of mind). Several studies have reported high levels of autistic symptoms in population with schizophrenia spectrum disorders. Our study systematically reviews and quantitatively synthetizes the current evidence on the presence of autistic symptoms in individuals with schizophrenia spectrum disorders. METHODS: A comprehensive literature search of the PubMed/MEDLINE, Cochrane Library, CINHAL, and Embase databases was performed from the date of their inceptions until March 2018. The primary outcome measure was the Autism Spectrum Quotient (AQ). As secondary outcome measures, we analysed the AQ subscales. Data were extracted and analyzed by using a conservative model and expressed by standardized mean difference (SMD). RESULTS: Thirteen studies comprising a total of 1958 individuals were included in the analysis. Results showed that individuals with schizophrenia spectrum disorders have higher levels of autistic symptoms compared to healthy controls [SMD: 1.39, 95% confidence interval (CI): 1.11 to 1.68] and lower levels of autistic symptoms compared to individuals with autism (SMD: -1.27, 95% CI: -1.77 to -0.76). CONCLUSIONS: Current findings support that individuals with schizophrenia spectrum disorders have higher autistic symptoms than healthy controls. Therefore, further studies are needed in order to shed light on the association between these two conditions.